Exercise alters liver mitochondria phospholipidomic profile and mitochondrial activity in non-alcoholic steatohepatitis - Gonçalves, Inês O. (2014)
Mitochondrial membrane lipid composition is a critical factor in non-alcoholic steatohepatitis (NASH). Exercise is the most prescribed therapeutic strategy against NASH and a potential modulator of lipid membrane. Thus, we aimed to analyze whether physical exercise exerted preventive (voluntary physical activity – VPA) and therapeutic (endurance training – ET) effect on NASH-induced mitochondrial membrane changes. Sprague-Dawley rats (n = 36) were divided into standard-diet sedentary (SS, n = 12), standard-diet VPA (SVPA, n = 6), high-fat diet sedentary (HS, n = 12) and high-fat diet VPA (HVPA, n = 6). After 9 weeks of diet-specific feeding, half of SS and HS group were engaged in an ET program for 8 weeks/5 day/week/1 h/day (SET, HET). Liver mitochondria were isolated for oxygen consumption and transmembrane-electric potential (ΔΨ) assays. Mitochondrial phospholipid classes and fatty acids were quantified through thin layer chromatography and gas chromatography, respectively, while cardiolipin (CL), phosphatidylcholine (PC) phosphatidylethanolamine (PE) and phosphatidylinositol (PI) molecular profile was determined by electrospray mass spectrometry. In parallel with histological signs of NASH, high-fat diet decreased PI, CL and PC/PE ratio, whereas PE and phosphatidic acid content increased in sedentary animals (HS vs. SS). Moreover, a decrease in linolelaidic, monounsaturated fatty acids content and an increase in saturated fatty acids (SFAS) were observed. Along with phospholipidomic alterations, HS animals showed a decrease in respiratory control ratio (RCR), ΔΨ and FCCP-induced uncoupling respiration (HS vs. SS). Both phospholipidomic (PC/PE, SFAS) and mitochondrial respiratory alterations were counteracted by exercise interventions. Exercise used as preventive (VPA) or therapeutic (ET) strategies preserved liver mitochondrial phospholipidomic profile and maintained mitochondrial function in a model of NASH.